Breaking Down COVID-19: A Living Textbook Publication of First Medicine and Global Clinical Partners (VITAE Academia Biomédica Digital, 2025)
The world is amidst a pandemic that is presenting one of the greatest public health challenges of the twenty-first century. A new coronavirus has jumped the interspecies barrier, and it possesses the capability of efficient person-to-person transmission and selectively kills older people and those with underlying chronic conditions. Since its emergence the new coronavirus has resulted in 43.7 million infections and over 1 million deaths as of October 25, 2020â€”20% of deaths are in the United States followed by Brazil (14%), India (10%), Mexico (7.8%), and the United Kingdom (4%).1The new disease emerged in December 2019 in Wuhan, China, and the early cases appeared to be associated with a local wholesale fish and live animal market.2 The cluster of patients exhibited respiratory features of pneumonia and acute respiratory distress syndrome as seen in the severe acute respiratory syndrome (SARS) coronavirus of 2002â€“2003, leading the scientists to suspect a virus of zoonotic origins. On December 31, the Chinese authorities informed the World Health Organization (WHO) of the outbreak, putting the organization on emergency footing.3 The WHO issued comprehensive technical guidance online with advise to all countries on how to detect, test, and manage emerging infections based on previous experience with SARS and the Middle East respiratory syndrome (MERS) outbreak of 2012.4 In mid-January, Chinese authorities announced a novel coronavirus with genetic structure similar to SARS (80%), and with its origins in bats, it was the cause of the new disease.5 The virus was officially named the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and the disease it caused the Coronavirus Disease 2019, or COVID-19.6Chinese authorities tried to contain the outbreak by imposing quarantines, social distancing, and testing, contact tracing, and isolating infected people. The entire Wuhan city of 11 million and Hubei Province of nearly 60 million, and later a quarter million people in other parts of China, were put under lockdown.7 But global transportation systems having morphed over a period of 100 years from slow trickles of population from one place to another to instantaneous shifts between continents made it difficult to contain outbreaks of COVID-19. Forty years earlier, the spread of HIV in the world had established how quickly a virus could spread between continents through simple air travel by an infected person. In this century, SARS, MERS, Zika, and the Ebola virus outbreaks all demonstrated the ease with which travelers could spread emerging pathogens. SAR-CoV-2 is no different, and it is even more efficient at transmission.8In the first 3â€“4 months of the outbreak, person-to-person transmission taking place before the infected person showed any symptoms of the disease, undetected cases of COVID-19 infection accounted for 79% of documented infections.9 In less than two months, SARS-CoV-2 went from a public health emergency to a disease of pandemic status, declared such on March 11, 2020, by WHO.10 At that time, there were 118,000 cases and 4291 deaths. Over 90% of cases were in just four countries: China (80,955 cases and 3162 deaths), Italy (10,149 cases and 631 deaths), Iran (8042 cases and 291 deaths), and South Korea (7755 cases and 60 deaths).11 But the number of cases in countries kept increasing rapidly.As SARS-CoV-2 spread rapidly encountering a population that hand no immunity and health-care systems that were unprepared, the virus claimed many lives. Although less deadlier than SARS, which had a case fatality rate of 10%, and the influenza pandemic of 1917 that had a mortality risk of 2%, COVID-19 appeared to be more deadly than seasonal influenza (0.1% mortality risk).12 Scientists estimated that the mortality risk for COVID-19 ranged from 0.2% to 1.0%, and was to increase substantially for people aged 60 years and older (6.38%) compared with those under 60 years (0.318%). The highest case fatality rates were seen in people in their 70s (8.61%) and 80s (13.4%) years of age.13 However, a number of other factors such as sex (males), chronic comorbidities such as diabetes, obesity, cardiovascular disease, hypertension, and other social determinants were emerging as risk factors for COVID-19 infection and mortality.14, 15As a new disease, COVID-19 required an effective response to slow down spread and prevent health systems from becoming overwhelmed. Countries implemented travel restrictions and full or partial lockdowns,16 which slowed down transmission but had devastating socioeconomic consequences and resulted in a global recession.17 Nonetheless, it was evident that basic public health measures such as testing, tracing, isolating infected cases and quarantining others, wearing facemasks, and practicing good hand hygiene were important interventions for reducing transmission and mortality.18 Over the past 10 months, promising new vaccines and a number of existing antiviral drugs and other treatments have emerged and are being used to manage the disease.19â€“21Since its interspecies jump, the global public health and medical communities have learned a lot about the virus. An unprecedented amount of information has been published on COVID-19, with tens of thousands of papers being made available for free.22 The sheer deluge of publications makes it difficult to keep up with the scientific literature and to assess the quality of publications given that many are in the form of preprints awaiting peer-review process. In the face of the flood of scholarly outputs, the impetus for putting together an online textbook is to make available, and easily accessible, information that has been carefully curated and reviewed from the public domain in one place, and to update it as new information comes forward. The COVID-19 Living Textbook is prepared by 55 experts (medical doctors, social scientists, and medical students, who are experts in their field and many of them have been working on the frontline of the COVID-19 response). It is aimed at a wide range of audiences, including clinicians, public health specialists, social scientists, and the general public. Twenty-four chapters cover a range of topics that are divided into four sections.Section 1: Chapters 1, 2, 3, and 4 introduce SARS-CoV-2 and COVID-19, and include the timeline of events; the virology and immunopathology, transmission, prevention; and risk factors for COVID-19; and outpatient management of mild to moderate infection.Section 2: Chapters 5â€“18, forming the bulk of the text, focus on the system responses by the body to COVID-19 and clinical management in hospitals, including in children and adolescents (Chapter 15). Chapter 17 discusses the management of severe cases of COVID-19, and Chapter 18, given the limited available data, examines postrecovery complications and long-term impacts, and compares it with the experience from SARS and MERS.Section 3: Chapters 19, 20, and 21 review the situation with personal protective equipment, diagnostics, and treatments and vaccines.Section 4: The final three chapters (Chapters 22â€“24) discuss the systemic discrimination and inequalities that put certain groups at greater risk for the disease, public policy making and leadership, and planning for future epidemics and pandemics as new viruses that make the interspecies jump to humans and begin another evolutionary path in a new host family.The COVID-19 pandemic, and the global response to it, has demonstrated that emerging and reemerging zoonotic diseases represent a public health challenge. It further reminds the global community about the impact of inequality, the gap between the â€œhavesâ€ and â€œhave-not,â€ and the importance of social determinants of health. Even in the largest economies of the world, including the United States of America, those groups with less opportunity including Blacks, Hispanics, and Native American have higher rates of mortality.23The legacy of COVID-19 will have long-lasting effects on society, including on the delivery of medicine. COVID-19 has ushered in, and with great success, telemedicine (TM) services.24 TM is being used to triage and treat basic illnesses, monitor chronic diseases, and diagnose mild cases of COVID-19. While the pandemic is an unfortunate occurrence, it provides an opportunity to set up an infrastructure to deliver health care to everyone in an equitable, convenient, and cost-effective manner.